Positivity of solutions of adapted generalized Riccati equation with consequences in oscillation theory. (July 2021) - Hasil, Petr; Veselý, Michal
Abstract: We present a new version of the adapted generalized Riccati transformation. This transformation leads to the Riccati equation for which we identify a simple condition guaranteeing the local positivity of its solutions. Using the condition, we obtain a new oscillation criterion for half-linear equations.